(Nitrato-κ2O,O′)bis[(E)-N-(pyridin-4-ylmethylidene-κN)hydroxyamine]silver(I) - Shan Gao (Acta Crystallographica Section E, 2012)
In the mononuclear title compound, [Ag(NO3)(C6H6N2O)2], the AgI atom is located on a twofold rotation axis and the nitrate-chelated AgI atom is further coordinated by two aromatic N atoms of hydroxylamine ligands in a distorted tetrahedral geometry. In the crystal, the nitrate ion has 2 symmetry with the N atom and one O atom located on the twofold rotation axis, and is linked to hydroxy groups of the hydroxylamine ligands by O—H...O hydrogen bonds, generating a chain running along the b axis.